2012
DOI: 10.1121/1.4731470
|View full text |Cite
|
Sign up to set email alerts
|

Unequal effects of speech and nonspeech contexts on the perceptual normalization of Cantonese level tones

Abstract: Context is important for recovering language information from talker-induced variability in acoustic signals. In tone perception, previous studies reported similar effects of speech and nonspeech contexts in Mandarin, supporting a general perceptual mechanism underlying tone normalization. However, no supportive evidence was obtained in Cantonese, also a tone language. Moreover, no study has compared speech and nonspeech contexts in the multi-talker condition, which is essential for exploring the normalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(85 citation statements)
references
References 28 publications
7
78
0
Order By: Relevance
“…Moreover, the perceptual performance was influenced by talker typicality in F0 range, despite the contextual F0 cues. This indicates that general contrast of auditory cues may not be sufficient for talker normalization in the perception of Cantonese level tones, which is consistent with the findings of previous studies (Chen & Peng, 2015;Francis et al, 2006;Zhang et al, 2012;Sjerps et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, the perceptual performance was influenced by talker typicality in F0 range, despite the contextual F0 cues. This indicates that general contrast of auditory cues may not be sufficient for talker normalization in the perception of Cantonese level tones, which is consistent with the findings of previous studies (Chen & Peng, 2015;Francis et al, 2006;Zhang et al, 2012;Sjerps et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…In two studies, Zhang et al (2012Zhang et al ( , 2013 further confirmed that the effects of speech and nonspeech context were unequal on the perception of Cantonese level tones, with a more careful design of the nonspeech context (using a triangle wave to generate the nonspeech context). The findings of Francis et al (2006) were largely replicated.…”
Section: Extrinsic Normalizationmentioning
confidence: 84%
See 1 more Smart Citation
“…Studies [3][4][5] have clearly demonstrated that the perception of Cantonese level tones is context-dependent. Francis et al [3] found that target stimuli were also more likely to be perceived as low-level tones when positioned in a synthesized context with high F0, whereas the same set of stimuli were perceived as high-level tones in a synthesized context with low F0.…”
Section: The Effect Of Speech Context On Lexical Tone Perceptionmentioning
confidence: 98%
“…As for word-external cues, they mainly refer to acoustic cues in the context, and are thus also known as Bcontextual cues^. Often, listeners make use of both word-internal F0 cues and contextual F0 cues for tone normalization [3][4][5][6]. But on some occasions, contextual cues with information about a talker's F0 range can be more crucial, such as when the stimuli to be categorized are highly ambiguous because they are located close to the perceptual boundaries of two tones.…”
Section: Introductionmentioning
confidence: 99%